2021
DOI: 10.1177/01945998211019306
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Preoperative Functional Status Prior to Major Head and Neck Surgery: A Pilot Study

Abstract: Objective To demonstrate feasibility of a recently developed preoperative assessment tool, the Vulnerable Elders Surgical Pathways and Outcomes Analysis (VESPA), to characterize the baseline functional status of patients undergoing major head and neck surgery and to examine the relationship between preoperative functional status and postoperative outcomes. Study Design Case series with planned data collection. Setting Two tertiary care academic hospitals. Methods The VESPA was administered prospectively in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Numerous studies have associated these measures with adverse postoperative outcomes. [13][14][15][16][17][18][19][20][21][22][23][24]27 Many of the tools used in these studies require additional evaluations outside the usual clinical care or specific equipment to perform measurements. For example, a validated frailty index requires a hand-held dynamometer for measurement of walking speeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have associated these measures with adverse postoperative outcomes. [13][14][15][16][17][18][19][20][21][22][23][24]27 Many of the tools used in these studies require additional evaluations outside the usual clinical care or specific equipment to perform measurements. For example, a validated frailty index requires a hand-held dynamometer for measurement of walking speeds.…”
Section: Discussionmentioning
confidence: 99%
“…28 Another tool, the Vulnerable Elders Surgical Pathways and Outcomes Assessment (VESPA), requires incorporation of the Mini-Cog, comorbidities, gait screening, and care team input. 17,27 Further, some of the previously reported tools, such as the Vulnerable Elders Survey 13 (VES-13), are only validated for older patients. 29 The picture is further complicated by the fact that some have shown that preoperative assessment tools, such as the Duke Activity Status Index, 30 may not be predictive of postoperative decline in patients undergoing major abdominal thoracic or abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%